Incidence and clinical presentation of myocardial ischemia in patients with chronic CAD in Italy: the ISPICA survey study. Issue 9 (September 2016) - Volterrani, Maurizio; Iellamo, Ferdinando; Marazzi, Giuseppe; Pusineri, Enrico; Guarini, Pasquale; Bonassi, Stefano; Caiazza, Francesco; Tramarin, Roberto; Chimini, Claudio; Proto, Cesare; ,
Abstract : Supplemental Digital Content is available in the text Abstract : Aim: This survey study was performed to provide an overall picture on the incidence of symptoms, with or without typical angina, in the real-life clinical practice and to identify clinical factors associated with atypical presentations in an unselected population of consecutive outpatients with chronic coronary artery disease (CAD). Methods: Thirty-six cardiology units located in different geographic areas of Italy enrolled a total of 1475 outpatients (73.6% men and 26.3% women; mean age 71 ± 10 and 67 ± 9 years in men and women, respectively) with a documented diagnosis of chronic CAD. Each patient underwent a medical history, with a detailed investigation as to the presence of typical angina or ischemic equivalents defined as sensation of chest pressure, or arm, neck, or jaw pain. Results: At admission, symptoms suggesting ischemic episodes were reported by 24.4% of patients. After an in-depth medical history collection by the specialist, the prevalence of combined typical or atypical myocardial ischemic episodes was ascertained in 39.3% of the overall population. Typical angina was reported by 13.6% of men and 22.7% of women ( P  < 0.0001), whereas ischemic equivalents were present in 7.3 and 12.9% of male and female patients, respectively ( P  < 0.001). Previous coronary artery bypass grafting (CABG; P  < 0.001) and fewer medical visits by cardiologists ( P  = 0.02) were independent predictors of atypical presentations. Conclusion: The ISPICA study shows that in an Italian population of real-world patients with chronic CAD, ischemic episodes, with both typical and atypical presentation, are still present in nearly 50% of patients, despite optimal medical therapy, and that atypical presentations of angina are linked to fewer visits by specialists and previous CABG. These findings would suggest to encourage patients with chronic CAD and general practitioners to consider more frequent cardiology specialist visits and to take into account the possibility of atypical presentations, particularly in patients with previous CABG.